2015
DOI: 10.1017/ice.2015.143
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Risk Factors for Multidrug-ResistantAcinetobacter baumanniiColonization Among High-Risk Nursing Home Residents

Abstract: OBJECTIVE To characterize the epidemiology of multidrug-resistant (MDR) Acinetobacter baumannii colonization in high-risk nursing home (NH) residents. DESIGN Nested case-control study within a multicenter prospective intervention trial. SETTING Four NHs in Southeast Michigan. PARTICIPANTS Case patients and control subjects were NH residents with an indwelling device (urinary catheter and/or feeding tube) selected from the control arm of the Targeted Infection Prevention study. Cases were residents coloni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
34
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 46 publications
5
34
0
4
Order By: Relevance
“…There were no subsequent outbreaks reported. Internationally, the prevalence of MDRA is much lower than that reported in studies from the US (prevalence of multidrug-resistant A baumannii was 15.0%) 40 and Australia (prevalence of multidrug-resistant A baumannii was 5.2%). 41 In RCHEs, the prevalence of MRSA is rising rapidly, and that of MDRA has the potential to rise.…”
Section: Discussionmentioning
confidence: 63%
“…There were no subsequent outbreaks reported. Internationally, the prevalence of MDRA is much lower than that reported in studies from the US (prevalence of multidrug-resistant A baumannii was 15.0%) 40 and Australia (prevalence of multidrug-resistant A baumannii was 5.2%). 41 In RCHEs, the prevalence of MRSA is rising rapidly, and that of MDRA has the potential to rise.…”
Section: Discussionmentioning
confidence: 63%
“…Cocolonization with more than one type of bacteria is common because some risk factors for colonization are common to multiple MDROs (30). One recent study found that among nursing home residents with indwelling devices, those colonized with multidrug-resistant Acinetobacter baumannii had a high likelihood of also being colonized with another antibiotic-resistant Gram-negative pathogen (31). Similarly, other studies have found that ICU patients colonized with VRE are often cocolonized with ESBLproducing bacteria or with MRSA (30,32).…”
mentioning
confidence: 99%
“…Bacterial colonization can be categorized as persistent carriage, intermittent carriage, or noncarriage (14). One study of nursing home residents with indwelling devices found that of the 15% who were colonized with multidrug-resistant Acinetobacter baumannii, nearly half of those colonizations recurred over time (31). Other studies have shown that among S. aureus nasal carriers, approximately 40% are persistently colonized and 60% are intermittently colonized (14).…”
mentioning
confidence: 99%
“…Interestingly, in a case-control study in the USA that aimed to characterize the epidemiology of MDR A. baumannii colonization in high-risk nursing home residents, 15% (n = 25) of residents were noted to be colonized, with all isolates being resistant to cephalosporins, monobactam (aztreonam), and quinolones. They reported the main risk factors for MDR A. baumannii as functional disability, Proteus mirabilis colonization, and diabetes mellitus [25].…”
Section: Accepted Manuscriptmentioning
confidence: 99%